Towards an archaeology of rubber: por uma arqueologia da borracha - Silva Alves Muniz, Tiago (Brasiliana: Journal for Brazilian Studies, 2021)
This article aims to address the impacts of rubber via historical and contemporary archaeology of the Amazon. Through an “archaeology of rubber” a notion of modernity is examined here. From the creation of rubber gloves to snow boots and tires, rubber has allowed humans to expand their interactions with the environment. As these interactions expanded, the consolidation of the Industrial Revolution and Occidentalism entangled actors in a complex web of meanings, becomings and agencies in opposition to local knowledge. Through a plural and multispecies approach, this article places the study of rubber’s materiality in the field of the archaeology of capitalism and modernity. Also, through oral history, deep archival research and public archaeology, local ontologies and materialities offer contemporary archaeology a more elastic view, aimed at widening perceptions of a global story.